Biodiesel purification by novel green solvent based on choline chloride: Deep eutectic solvent. Issue 2 (20th December 2021) - dos Santos, Matheus Romeiro Manoel; Teleken, Joel Gustavo; Tavares, Fernanda; da Silva, Edson Antonio
Abstract: In the typical biodiesel production process carried out by the wet method, large volumes of effluents are generated. The objective of this work was to evaluate and compare the use of a novel high efficiency deep eutectic solvent (DES), with the conventional solvent (hot water). The intense ionic interactions established with the formation of hydrogen bonds between DES and impurities, especially with OH groups, potentiated the use of DES, reducing the levels of moisture, free and total glycerol, and mono, di‐ and triglycerides, in accordance with the standards EN 14214 and ASTM D6751, and being more efficient than conventional purification in some cases. The use of triethylene glycol in the DES composition reduced the content of triglyceride, a poorly soluble molecule. Therefore, with a simple and efficient technique, this work presents the potential use of a new alternative green solvent, which can help reduce costs for biodiesel purification. Abstract :